2014
DOI: 10.1186/bf03352497
|View full text |Cite
|
Sign up to set email alerts
|

Continuous dynamic response along a pre-existing structural discontinuity induced by the 2001 eruption at Mt. Etna

Abstract: The intrusive process of the 2001 Mt. Etna eruption was accompanied by marked ground deformation and relevant seismic activity recorded between 12 and 17 of July (INGV-CT, 2001). At the same time, extensometer data evidenced the re-activation of a dry surface failure zone on the high south-eastern sector of Mt. Etna; this fracture system, formed in 1989, has been related to the propagation of a shallow blade-like dike along a NNE-SSW discontinuity (Bonaccorso and Davis, 1993;Bianco et al., 1998). The NNW-SSE d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…In particular, high V p anomaly in the velocity structure (Patanè et al 2002), low Q p (Martinez-Arevalo et al 2005) and negative gravity anomaly (Carbone et al 2003) have been observed in the sector Z2. Moreover, ground deformations observed by GPS (Bonforte et al 2004) show a pattern compatible with a dyke intrusion, and extensometer data (Gambino 2004) collected slightly east of Z2, highlight ground movements that are in agreement with the mechanism proposed here.…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, high V p anomaly in the velocity structure (Patanè et al 2002), low Q p (Martinez-Arevalo et al 2005) and negative gravity anomaly (Carbone et al 2003) have been observed in the sector Z2. Moreover, ground deformations observed by GPS (Bonforte et al 2004) show a pattern compatible with a dyke intrusion, and extensometer data (Gambino 2004) collected slightly east of Z2, highlight ground movements that are in agreement with the mechanism proposed here.…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 87%
“…Etna volcano. The main feeding mechanism just described is consistent with almost all the observations made, but seismic activity (Patanè et al 2002;Musumeci et al 2004), gravity observations (Carbone et al 2003), GPS measurements (Bonforte et al 2004) and extensometer data (Gambino 2004) highlight a complex behaviour that cannot be explained by one simple intrusion mechanism, because all the geophysical information also points to important phenomena in a volume located 2-3 km SE from the eruptive scenario.…”
Section: Introductionsupporting
confidence: 79%
“…Later on (in terms of weeks or months) the cumulated stress was released, and the ground deformation propagated to the eastern periphery of the volcano. The propagation started from the upper southeastern flank, along a NNW‐SSE fault near the intrusive dike, as already detected early during the intrusion [ Gambino , 2004] and during the first days of the eruption by Bonforte et al [2004].…”
Section: Discussionmentioning
confidence: 84%
“…Effusive activity started in the late evening of 17 July due to the intrusion of a vertical dike [e.g., Acocella and Neri , 2003; Behncke and Neri , 2003]. Field measurements [ Billi et al , 2003; Lanzafame et al , 2003] along with ground deformation and seismic data [e.g., Gambino , 2004] documented the dynamic response of the NNW–SSE system during the final stage of the dike intrusion.…”
Section: Introductionmentioning
confidence: 99%